Faktor-Faktor Yang Berpengaruh Terhadap Kunjungan Bayi Balita Ke Pusat Kesehatan Masyarakat Di Kelurahan Tarus Kecamatan Kupang Tengah Kabupaten Kupang Tahun 2014 - Tirza Vivianri Isabela Tabelak; Serlyansie V. Boimau (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Background: Indicators related to child health are important indicators in determining the overall health status of the community, especially assessing the success of health services and development in the health sector. These indicators are infant mortality (IMR) and Under-five Mortality Rate (AKABA). The government has organized health services known as Maternal and Child Health Services. Tarus' Maternal and Child Health Services in 2011 saw 72.22 percent of infants under five who visited Maternal and Child Health Services. In 2012 the number of infant visits to Maternal and Child Health Services decreased by 69.3 percent (Health Center Health Profile, 2012) out of 3,695 toddlers in Tarus Maternal and Child Health Services work areas there were only 2,563 (69.3 percent) toddlers who use Maternal and Child Health Services every month. Research Objectives: To find out the factors that influence the visit of Toddler Babies to Maternal and Child Health Services in Tarus Village, Kupang Tengah District, Kupang Regency. Research Method: Type of descriptive research. A total of 32 respondents were parents of infants under five. The research instrument uses a questionnaire. Research Results: Knowledge factor 81.2 percent good. As many as 62.5 percents of mothers have children under five years old. Conclusion: Knowledge factors and the number of children do not directly affect the visit of infants to Maternal and Child Health Services. Other factors that influence our attitudes, behavior, the role of Maternal and Child Health Services cadres, community participation and lack of support or cooperation in participation from other sectors.